(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Italian Law no. 219/2017, containing provisions on informed consent and advanced directives, represents the landing place that the Italian legislature has reached following a long debate in relation to the issues of end of life and living wills. Although many authors have given the law a positive reception, some critical aspects have arisen, such as the issue of conscientious objection for healthcare professionals. Recognizing that the debate is far from being resolved, this article highlights the controversial aspects of conscientious objection as covered by Law no. 219/2017, but also the more general regulatory assumptions regarding this issue.